2017
DOI: 10.1111/plb.12586
|View full text |Cite
|
Sign up to set email alerts
|

Radial oxygen loss by the cushion plant Eriocaulon schimperi prevents methane emissions from an East‐African mountain mire

Abstract: Groundwater-fed fens are known sources of methane (CH ) emissions to the atmosphere, and these are known to be mediated by the vegetation. In a fen located in the Bale Mountains, Ethiopia, we assessed the effects of a cushion plant (Eriocaulon schimperi) and a sedge (Carex monostachya) on rhizosphere biogeochemistry. Methane and CO concentrations and pH were measured in pore-water at different depths in the profile. Redox potentials and NaCl-extractable element concentrations were analysed in soil samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…These findings agree with previous research by Fritz et al (2011), who observed CH 4 emissions from Astelia lawns at a low magnitude compared to that presented here and presented a similar CH 4 concentration depth profile. Extremely low CH 4 concentrations have also been obtained by Dullo et al (2017) in upper peat layers of an Ethiopian cushion bog. Nevertheless, in deep peat layers below the rhizosphere, CH 4 concentrations of our study approached magnitudes reported for Chilean bogs with mixed vegetation consisting of Sphagnum mosses and A. pumila (Broder et al, 2015).…”
Section: Astelia Lawns -Zero Emission Scenariomentioning
confidence: 90%
See 3 more Smart Citations
“…These findings agree with previous research by Fritz et al (2011), who observed CH 4 emissions from Astelia lawns at a low magnitude compared to that presented here and presented a similar CH 4 concentration depth profile. Extremely low CH 4 concentrations have also been obtained by Dullo et al (2017) in upper peat layers of an Ethiopian cushion bog. Nevertheless, in deep peat layers below the rhizosphere, CH 4 concentrations of our study approached magnitudes reported for Chilean bogs with mixed vegetation consisting of Sphagnum mosses and A. pumila (Broder et al, 2015).…”
Section: Astelia Lawns -Zero Emission Scenariomentioning
confidence: 90%
“…Soil-atmosphere CH 4 fluxes were calculated from the gas concentration increase over time within the chamber using the software package (MATLAB Release R2015a) routine described in Eckhardt and Kutzbach (2016) and Kutzbach et al (2007). Gas concentration was modelled as either a linear or exponential function of time.…”
Section: Ch 4 Flux Calculation and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the few studies that have been carried out in intact cushion peatlands, cushion plant peatlands have been found to have very low CH4 flux rates, which has been attributed to high oxidation by cushion plant roots (Fritz et al 2011;Dullo et al 2017;Sanchez et al 2017).…”
Section: Introductionmentioning
confidence: 99%